The Role of Forensic Science in Proving Murder Cases at the Investigation Stage - Arif, Muhammad; Abdaud, Faisal; Huzaiman, Huzaiman (Fakultas Syariah INSURI Ponorogo, 2023)
Forensics is a science that has a crucial role in the judicial process through examination and collection of physical evidence found at crime scenes. The involvement of forensic experts at crime scenes usually occurs in significant cases, where they are only called upon request from the authorities. This study aims to study the role of forensic medicine in helping investigators find material truth in murder cases, as well as identify possible obstacles. Through a library legal research and descriptive approach, secondary data such as legal documents and literature are analyzed to provide a clear and detailed picture of role of forensic science in assisting investigators in finding the material truth in murder cases and asserting the obstacle of it. The results showed that forensic medicine has a crucial role in uncovering material truths and providing legitimate evidence in murder cases. However, lack of coordination between law enforcement officials and forensic doctors can be an obstacle. Therefore, good cooperation and coordination between law enforcement officials and forensic doctors is the key to success in handling this case. The principle of justice must be upheld in the investigation process.